Comparison of laparoscopic versus open radical hysterectomy in patients with early-stage cervical cancer: a multicenter study in China. Issue 8 (22nd June 2020) - Hu, Ting wen yi; Huang, Yue; Li, Na; Nie, Dan; Li, Zhengyu
Abstract : Introduction: Recently, the safety of minimally invasive surgery in the treatment of cervical cancer has been questioned. This study was designed to compare the disease-free survival and overall survival of abdominal radical hysterectomy and laparoscopic radical hysterectomy in patients with early-stage cervical cancer. Methods: A total of 1065 patients with early-stage cervical cancer who had undergone abdominal/laparoscopic radical hysterectomy between January 2013 and December 2016 in seven hospitals were retrospectively analyzed. The 1:1 propensity score matching was performed in all patients. Patients with tumor size ≥2 cm and <2 cm were stratified and analyzed separately. Disease-free survival and overall survival were compared between matched groups. After conﬁrming the normality by the Shapiro-Wilks test, the Mann-Whitney U test and the χ 2 test were used for the comparison of continuous and categorical variables, respectively. The survival curves were generated by the Kaplan-Meier method and compared by log-rank test. Results: After matching, a total of 812 patients were included in the disease-free survival and overall survival analyses. In the entire cohort, the laparoscopic radical hysterectomy group had a significantly shorter disease-free survival (HR 1.65, 95% CI 1.00 to 2.73; p=0.048) but not overall survival (HR 1.60, 95% CI 0.89 to 2.88; p=0.12) when compared with the abdominal radical hysterectomy group. In patients with tumor size ≥2 cm, the laparoscopic radical hysterectomy group had a significantly shorter disease-free survival (HR 1.93, 95% CI 1.05 to 3.55; p=0.032) than the abdominal radical hysterectomy group, whereas no significant difference in overall survival (HR 1.90, 95% CI 0.95 to 3.83; p=0.10) was found. Additionally, in patients with tumor size <2 cm, the laparoscopic radical hysterectomy and abdominal radical hysterectomy groups had similar disease-free survival (HR 0.71, 95% CI 0.24 to 2.16; p=0.59) and overall survival (HR 0.59, 95% CI 0.11 to 3.13; p=0.53). Conclusion: Laparoscopic radical hysterectomy was associated with inferior disease-free survival compared with abdominal radical hysterectomy in the entire cohort, as well as in patients with tumor size ≥2 cm. For the surgical treatment of patients with early-stage cervical cancer, priority should be given to open abdominal radical hysterectomy.